Featured Article: Dexamethasone and rosiglitazone are sufficient and necessary for producing functional adipocytes from mesenchymal stem cells. (September 2015) - Contador, David; Ezquer, Fernando; Espinosa, Maximiliano; Arango-Rodriguez, Martha; Puebla, Carlos; Sobrevia, Luis; Conget, Paulette
The final product of adipogenesis is a functional adipocyte. This mature cell acquires the necessary machinery for lipid metabolism, loses its proliferation potential, increases its insulin sensitivity, and secretes adipokines. Multipotent mesechymal stromal cells have been recognized as a source of adipocytes both in vivo and in vitro . The in vitro adipogenic differentiation of human MSC (hMSC) has been induced up to now by using a complex stimulus which includes dexamethasone, 3-isobutyl-1-methylxanthine, indomethacin, and insulin (a classical cocktail) and evaluated according to morphological changes. The present work was aimed at demonstrating that the simultaneous activation of dexamethasone's canonical signaling pathways, through the glucocorticoid receptor and CCAAT-enhancer-binding proteins ( C/EBPs ) and rosiglitazone through peroxisome proliferator-activated receptor gamma ( PPAR-gamma ) is sufficient yet necessary for inducing hMSC adipogenic differentiation. It was also ascertained that hMSC exposed just to dexamethasone and rosiglitazone (D&R) differentiated into cells which accumulated neutral lipid droplets, expressed C/EBP-alpha, PPAR-gamma, aP2, lipoprotein lipase, acyl-CoA synthetase, phosphoenolpyruvate carboxykinase, adiponectin, and leptin genes but did not proliferate. Glucose uptake was dose dependent on insulin stimulus and high levels of adipokines were secreted (i.e. displaying not only the morphology but also expressing mature adipocytes' specific genes and functional characteristics). This work has demonstrated that (i) the activating C/EBPs and PPAR-gamma signaling pathways were sufficient to induce adipogenic differentiation from hMSC, (ii) D&R producing functional adipocytes from hMSC, (iii) D&R induce adipogenic differentiation from mammalian MSC (including those which are refractory to classical adipogenic differentiation stimuli). D&R would thus seem to be a useful tool for MSC characterization, studying adipogenesis pathways and producing functional adipocytes.